Ruling on Financial Fines for Violating Healthy Procedures Taken to Prevent Corona Disease in Islamic Jurisprudence (Islamic Sciences Journal, 2023)
ABSTRACT                          Physicians and specialists in the field of health have determined the means and health rules that must be adhered to at the time of the epidemic of infectious diseases, and it is obligatory for citizens to adhere to all health procedures, and not to violate the laws issued by the higher authorities of the state regarding the prevention of diseases, especially restricting the preventive precautionary measures taken against Corona disease: namely: A disease that affects the respiratory system and is called (Covid 19), including restricting to the wearing of a mask, quarantine and fines for violators. To limit the spread of this dangerous epidemic, this punishment is imprisonment and a fine from violators of these laws and returning it to the interests of Muslims.        I talked about the legal ruling for taking procedures against the Corona epidemic, Contemporary scholars have agreed on the necessity of taking measures and enacting rulings when the Corona epidemic appears in a region, governorate or country, and the matter in that is due to the specialists of doctors, and the competent state institutions, and citizens must respond For all the  procedures  issued by the official authorities, to prevent the spread of the epidemic and its spread. The guardian and the competent authorities have the right to compel people to take certain  procedures  to save lives and protect the soul from diseases.